DESAIN SISTEM INSTRUMENTASI PROSES DISTILASI FRAKSINASI BATCH BERBASIS KENDALI SUHU - Muhammad Arman; Agus Prasetya; Sihana - (ASEAN Journal of Systems Engineering, 2014)
Distillation column is a column that is widely used in both large industry and small and medium industries. Use of distalasi column on small and medium industries such as the distillation of essential oils. In the subsequent use of the distillation column used for purification or further process to obtain a higher quality product in the form of multstage distillation. In the process of multistages distillation,  temperature is an important component in the process, because of that controls the temperature has an important role. Temperature controllers available today are manual, which causes frequent inaccuracy of the distillation process, resulting in low product quality. Therefore automatic temperature control is required.In this thesis, instrumentation system of fractionation distillation process based of temperature control are designed. The design process notice the six important  point temperature in the distillation process, using a thermocouple as a temperature sensor, and LM35 as the cold junction temperature,  the 6218 USB as Data Acquisition Board, and the software LABVIEW 2010.The instrumentation system programming, displays the temperature from time to time at intervals of one second, the temperature statistics (min, max and average) as well as measurement results table. The program also features a choice (shaped slider) to  set the temperature for a flexible batch process. The response characteristics of the instrumentation system is less than one second, both in displaying measured data, response indicator, display graphs, and data tables. The instrumentation system is also designed to regulate the flow rate of the cooling water and container replacement indicator for each product distillation.